Implementation of the Prosecutors' Code of Ethics in Indonesia's Judicial System: A Case Study of Pinangki Sirna Malasari - Hillan Rusydha Fazha; Fauzan Adhima; Muhammad Fawwaz Akbar; Dicky Dwi Angga F.; Arief Budiono (Journal of Human Interaction and Social Studies, 2026)
The 1945 Constitution of the Republic of Indonesia establishes Indonesia as a state based on the rule of law, requiring prosecutors to exercise their authority in accordance with legal and ethical principles. This study analyzes the implementation of the Prosecutors' Code of Ethics through the case of Pinangki Sirna Malasari. The research employs a non-empirical normative juridical approach combined with a case study method by examining statutory regulations, judicial decisions, legal doctrines, and academic literature. The findings indicate that Indonesia possesses a comprehensive regulatory framework through Law Number 11 of 2021 and Attorney General Regulation Number PER-014/A/JA/11/2012, but its implementation remains constrained by weaknesses in supervision, accountability mechanisms, and consistent ethical enforcement. The Pinangki case demonstrates that prosecutorial misconduct is not merely an individual criminal act but also reflects broader institutional governance problems that undermine public trust in the justice system. Strengthening prosecutorial integrity requires preventive ethical governance, transparent disciplinary procedures, continuous professional ethics education, and stronger coordination between internal supervisory bodies and independent oversight institutions.